Gestão das relações interpessoais, person-environment fit e turnover: um estudo nas “Melhores Empresas para Trabalhar” de 2017 - Carli , Danielle Deimling de (2019)
This study examines whether Fit Person-Environment Fit (PE FIT) mediates the relationship between Interpersonal Relationship Management Practices and Employee Turnover in the “Best Companies to Work For” in Brazil in 2017. It is classified as quantitative and descriptive by data survey or cross-sectional survey. The population and survey sample included 456 companies that participated in the ranking of the “Best Companies to Work For” in Brazil in 2017, according to a database collected in 2017 and published in 2018 by Fundação Instituto de Administração (FIA) and Exame Magazine guide. Data from 456 companies were used to analyze Interpersonal Relationship Management Practices and Turnover indexes and the perceptions of the 250.273 employees who answered the questionnaire, consisting of 70 variables, which represents the Quality Indexes in the Workplace (IQTA), taken in this work as PE FIT. The Interpersonal Relations Practices variable was outlined in a staggered manner, giving points for each of the practices declared by company. P-E FIT, after factor analysis, was represented by its four dimensions: Person-Job Fit (P-J FIT), Person-Organization Fit (P-O FIT), Person-Group Fit (P-G FIT) and Person-Supervisor Fit (P-S FIT). Pearson r correlation analysis, linear regression, followed by tests Sobel, Aroian and Goodman were used for effect mediation. Organized the dependent variable, independent and mediators, it was evaluated if the set of Interpersonal Relations Practices affect the Turnover indexes of the researched organizations and this relationship was confirmed (H1), and the higher the incidence of these practices, the lower the indexes of Turnover. It was then found that the existence of Interpersonal Relationship Management practices impacts the P-E FIT on its four dimensions (H2a, H2b, H2c and H2d). However, regarding the effect of mediating the dimensions of the PE-FIT variable between the set of Interpersonal Relations Practices and Turnover indicators, it was identified that only P-O FIT (H3c) can be considered as a mediator, rejecting mediation of the PJ-FIT variables (H3b); P-G FIT (H3d) and P-S FIT (H3a). Limitations and suggestions for future work are presented at the end of this study.